Pengolahan Sampah Organik Rumah Tangga melalui Biokonversi Berkelanjutan dengan Memanfaatkan Larva Black Soldier Fly (Diptera: Stratiomyidae) di Ngadilegi Utara - Agustya Salma Choerunnisa; Ardhia Pramesti Cahyani; Ramadhani Mahendra Kusuma (Universitas Kristen Indonesia Toraja, 2024)
This program encapsulates comprehensive efforts undertaken by Bina Desa in North Ngadilegi, focusing on community-oriented initiatives such as Focus Group Discussions (FGD), the fabrication of waste sorting buckets, and counseling sessions addressing waste sorting and maggot cultivation. The counseling sessions, attended by a diverse group of 33 residents, including village officials, housewives, farmer groups, and youth organizations, aimed to instill knowledge and enthusiasm for sustainable waste management practices. The community's active participation underscores the potential impact of maggot cultivation in mitigating household organic waste while concurrently enhancing economic prospects. Maggot cultivation, particularly utilizing Black Soldier Fly (BSF) larvae, emerged as a promising solution for this problem. The study underscores the ease of BSF breeding and its affinity for organic waste, presenting a valuable opportunity for community-based waste management. The residents' demonstrated enthusiasm signifies a positive reception to the initiatives, fostering optimism for long-term adoption. The collective activities orchestrated by Bina Desa lay a foundation for holistic community development, emphasizing environmentally friendly practices and economic sustainability. As the program seeks to expand waste sorting and maggot cultivation infrastructure, it envisions a future where each household contributes to sustainable waste management, concurrently realizing economic benefits. This study contributes to the discourse on community-based waste management strategies and highlights the potential of maggot cultivation as a transformative solution for both waste reduction and local economic development.